PERSEPSI GURU TENTANG PEMBELAJARAN DARING - Mena Niman, Erna (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
This study aims at revealing teacher perceptions and the impact of online learning during the Covid-19 pandemic. The research method used was survey research with a questionnaire as a data collection instrument. The results showed that teachers had a negative perception of online learning. This is evidenced by 92.3% of respondents' answers who consider online learning to be ineffective and only 7.7% of respondents' answers gave positive responses. This condition is mostly caused by the lack of face-to-face interaction between students and teachers, the network and the availability of inadequate online learning facilities and the lack of parental attention to the child's learning process. This research is useful for improving teacher learning strategies, the attention of parents and all parties directly involved in the education process of students.